2019
DOI: 10.29332/ijssh.v3n2.340
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Principle Implementation between Teachers and Students Indonesian Language Teaching Case

Abstract: This research aimed to explain the context of learning by applying the principles of cooperation during the teaching and learning process in the classroom, and the relationship of working principles between teachers and students. This study used a qualitative descriptive approach. The research subjects were Indonesian language teachers and students in Tampaksiring Senior High School 1. To gain data, the methods of recording, observation, and interview were applied. Data analysis was conducted with three stages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 6 publications
(13 reference statements)
1
7
0
Order By: Relevance
“…In addition, the process of interactional communication by English teachers implemented quality maxim by involving objective evidence. Previous study emphasize that the maxim of quality in English activities requires teachers and students to express the utterance with sufficient proof (Widiasri et al, 2019). The interaction between English teachers and students using maxim quality needs to provide actual situations to avoid misunderstanding (Bakoko & Pratiwi, 2021;Wahyudi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the process of interactional communication by English teachers implemented quality maxim by involving objective evidence. Previous study emphasize that the maxim of quality in English activities requires teachers and students to express the utterance with sufficient proof (Widiasri et al, 2019). The interaction between English teachers and students using maxim quality needs to provide actual situations to avoid misunderstanding (Bakoko & Pratiwi, 2021;Wahyudi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The experiment consductor gives questionnaires and instructions, observes, listens, and records the activities of each individual selected, and records discussions and debates of teachers and students to find out about beliefs, attitudes, thinking activities, ideas sharing in groups and the solutions of those groups. The above factors will be the basis for qualitative assessment of understanding, teaching and learning ability from the teaching point of view of teachers and students (Widiasri et al, 2019;Tuarez et al, 2019).…”
Section: Methods Of Pedagogical Experimentsmentioning
confidence: 99%
“…In the classroom interaction, the breaking of the Grice maxims also appears. Widiasri et al (2019) found out that, from four maxims, the classroom interaction at the senior high school level broke the maxim of quality, quantity, and manner. Concerning gender, Khayati et al (2019) found that maxim of manner was flouted in teachers' interaction with male and female students.…”
Section: Gender and Maxims Breaking In The Classroom Interactionmentioning
confidence: 99%